SUBJECTIVE PERCEPTION OF AN INDIVIDUAL WITHIN SOCIALISATION PROCESS - Vorobjovs, Aleksejs; Skuja, Ilona; Ābelīte, Larisa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This a pilot study where the study method “Autoidentification and Identification Method According to Oral Portrayals of Character”. Contemporary psychological studies show that a person’s behaviour in social context is not only simple consequences of the objective conditions having effect on him or her, it significantly depends on subjective perception and interpretation of the aggregate of external events, i.e., determination of situation carried out by an individual. Autoidentification method according to oral portrayals of character (Эйдемиллер, 1973) was used for diagnosing the personality and image of “I” accentuation types. The pilot study involved two groups of adolescents; one group included adolescents with deviant behaviour (n=60, 39 boys, 21 girl) but the second group included adolescents without actual behaviour disorders (n= 60, 35 boys, 25 girls). The study allowed determination of differences between the results presented by both groups with constituting grounds for performing further empiric study with a larger selection of study in the future.